Antidoping program: An important factor in the promotion and protection of the integrity of sport and athlete`s health - Mazzeo, F.; Monda, V.; Santamaria, S.; Nigro, E.; Valenzano, A.; Villano, I.; Cibelli, G.; Messina, A.; Messina, G. (The Journal of Sports Medicine and Physical Fitness, 2018)
Using performance-enhancing drugs concerns not only elite Olympic and Paralympic Games` athletes but also amateur athletes, who are making increasing use of substances and/or methods. Furthermore, a new frontier reached by the doping is the use of genes. World Anti-Doping Agency expressly prohibited the participation in competitive sports by the athlete in case of taking banned substances to treat disease in the event that the above assumption implies an excessive improvement of performance. This study aims to analyze and show the doping control as an essential part of the antidoping program to promote and protect the integrity of sport and athlete`s health. Testing is carried out in accordance with the World Anti-Doping Code (WADC) and several international standards (ISs). The ISs were developed for laboratories, testing, the prohibited list, and for therapeutic use exemptions. It seems that the 2009 version of the WADC obliges all the healthcare professionals not to assist athletes engaged in doping behaviours; they can be removed from working with athletes. Many people do not know doping`s dangerous effects on health. It is necessary, therefore, to implement the knowledge on this issue through public and sports institutions information and awareness campaigns. For this reason, local institutions and the National Olympic Committee shall give tools, in particular economic, to carry out the work of education, training, and control.